Taking it seriously: commitments to the environment in South-South preferential trade agreements. Issue 6 (19th September 2022) - Lechner, Lisa; Spilker, Gabriele
ABSTRACT: Conventional wisdom suggests that preferential trade agreements (PTAs) contain environmental standards because the highly regulated North imposes these standards on the reluctant South. But what about the increasing occurrence of environmental standards in South-South trade agreements? Are they simply a product of a diffusion process from North-South PTAs? Or do environmental standards in South-South PTAs signal real commitment to both environmental regulation and performance? We test these two perspectives against each other by quantitatively examining original data on environmental provisions in 479 PTAs. Using performance-based indicators our results support the notion that if developing countries take on the obligation of committing to environmental. When relying on a measure on commitment levels in the Paris Agreement on Climate Change, the results rather point to the diffusion-based perspective. In contrast to the conventional wisdom, the study shows that environmental protection is not always extrinsically motivated by developed countries.